SUFISM IN THE MODERN AND CONTEMPORARY IRANIAN POLITICS - BĂDESCU, Șerban-P. (Studia Universitatis Babes-Bolyai Studia Europaea, 2023)
The objective of this article is to explore how political Sufism, in conjunction with political Shī’ism, influences contemporary Iranian internal and external affairs, the decision-making process, and the future political ideology. While religion has consistently been an integral part of Iranian state and culture, the primary faith has not always played a definitive role in political decisions throughout history, particularly in recent decades. To gain a deeper understanding of Iranian politics and its future trajectory, it is essential to comprehend the role of Sufi elements within it. This work elucidates the core political Sufi ideas and their persistence and development within Persian borders up to the present day, despite facing substantial opposition from the ulama. Furthermore, in order to identify these Sufi elements within the current Iranian political landscape, the article analyzes all presidential administrations since the Revolution and highlights how political Sufism has become ingrained in both the decision-making process and political propaganda.